An Analysis of Anatomy Education Before and During Covid‐19: May–August 2020. Issue 2 (12th February 2021) - Harmon, Derek J.; Attardi, Stefanie M.; Barremkala, Malli; Bentley, Danielle C.; Brown, Kirsten M.; Dennis, Jennifer F.; Goldman, Haviva M.; Harrell, Kelly M.; Klein, Barbie A.; Ramnanan, Christopher J.; Richtsmeier, Joan T.; Farkas, Gary J.
Abstract : Coronavirus disease 2019 (Covid‐19) created unparalleled challenges to anatomy education. Gross anatomy education has been particularly impacted given the traditional in‐person format of didactic instruction and/or laboratory component(s). To assess the changes in gross anatomy lecture and laboratory instruction, assessment, and teaching resources utilized as a result of Covid‐19, a survey was distributed to gross anatomy educators through professional associations and listservs. Of the 67 survey responses received for the May–August 2020 academic period, 84% were from United States (US) institutions, while 16% were internationally based. Respondents indicated that in‐person lecture decreased during Covid‐19 (before: 76%, during: 8%, P < 0.001) and use of cadaver materials declined (before: 76 ± 33%, during: 34 ± 43%, P < 0.001). The use of cadaver materials in laboratories decreased during Covid‐19 across academic programs, stand‐alone and integrated anatomy courses, and private and public institutions ( P ≤ 0.004). Before Covid‐19, cadaveric materials used in laboratories were greater among professional health programs relative to medical and undergraduate programs ( P ≤ 0.03) and among stand‐alone relative to integrated anatomy courses ( P ≤ 0.03). Furthermore, computer‐based assessment increased ( P < 0.001) and assessment materials changed from cadaveric material to images ( P < 0.03) during Covid‐19, even though assessment structure was not different ( P > 0.05). The use of digital teaching resources increased during Covid‐19 ( P < 0.001), with reports of increased use of in‐house created content, BlueLink, and Complete Anatomy software ( P < 0.05). While primarily representing US institutions, this study provided evidence of how anatomy educators adapted their courses, largely through virtual mediums, and modified laboratory protocols during the initial emergence of the Covid‐19 pandemic.